The relationship between classroom projects and the students attitudes towards english in the eighth year of basic education at Carlos Rigoberto Vintimilla School in Cuenca, in the first term, 2014-2015 school year - Pauta Romero, Miriam Soledad (2016)
This research offers a deeply analysis of the relationship between the classroom projects and the students' attitude towards English by applying a descriptive method as well as a field research. The instrument for data collection was the survey by the means of questionnaires applied to students. The methodological design was correlational, quantitative and transversal.The participants of this investigation are students in 8th year of EGB. Therefore, it was analyzed the different resources of information gotten from teachers and students referring to the teaching-learning strategies, students' motivation, students' attitude, and classroom innovation, etc.The analyzed data suggested the fact that exist an influence of the classroom projects in the students' attitude towards the English language, the challenge of teachers and students to manage and discover new teaching and learning tools which promote a dynamic learning environment and increase students' motivation.Besides, the analysis showed that there is a crucial relationship between the variables. The important aspect is that the students prefer to learn in a fun way with the intermediation of educational resources that transforms the learning process in an innovative experience and in that way the pupils get a better academic achievement.